DIALOGUE SKILLS IN DRAMA LESSONS AT SCHOOL - Riansyah, Gugum Okta; Boeristwati, Endry; Lustyantie, Ninuk (Erudio Journal of Educational Innovation, 2024)
Understanding language skills in the Merdeka Curriculum is explained in each element consisting of four elements, namely listening, reading and viewing, speaking and presenting, and writing. In the F phase element of Indonesian language learning outcomes, speaking and presenting aim to enable students to present ideas, thoughts, and creativity in language in the form of a logical, systematic, critical, and creative dialogue. The dialogue skills in drama subject at school still need to be further developed. Speaking skills in drama dialogue need to be trained with exercises and special techniques. The purpose of this research is to describe the dialogue skills in drama subject. The research method used is using qualitative methods with descriptive analysis and data collection techniques through literature studies obtained from various books, scientific articles, previous research, and data related to dialogue subject in drama. In the results and discussion, it explains the concept of dialogue in drama, steps to dialogue, and aspects of dialogue. Based on the findings obtained by researchers in the field and through literature studies, it can be concluded that the dialogue skills in drama subject needs to be further studied so that learning outcomes can be carried out. The dialogue skills in drama is closely related to speaking skills which are important skills for students to train students’ thinking abilities and be able to accurately find information implied in a story and make that information as material in conveying messages through scripts in drama.